Study of the Gender Roles in Modern Spanish from a Gender Perspective - Qiu, Manqing (Journal of the University of Zulia, 2023)
Research on teaching materials of ELE for Chinese speakers often ignores gender aspects. This study focuses on analyzing the representation of the roles of women and men in the 105 texts in Modern Spanish, with the aim to find out whether the teaching materials have a gender perspective. This work studies identities and relationships/qualities to clarify the path of study. Using the 105 texts collected and the content analysis, we verified that the Modern Spanish collection barely obtains a gender perspective. The inequality is aggravated due to the following aspects: (1) the lack of female characters; (2) women’s professional and family identities are ignored and disparaged; (3) the feminine character is stigmatized in the way of word expression. Therefore, we conclude that, the roles of women are discriminated against, stereotyped, and subordinate. It’s essential to train teachers and students in the area of ELE with a gender perspective, to effectively capture and remove the androcentrism from didacticism and learning. Thus, an inclusive language environment will be built that will improve the incorporation of equality into today’s society.